2012
DOI: 10.1902/jop.2011.110456
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Versus External Abutment Connection Modes on Crestal Bone Changes Around Dental Implants: A Radiographic Analysis

Abstract: Within the limitations of this study, the implant-abutment connection technology appears to have a significant impact on peri-implant CBLs, with the external connection paralleled by a significant reduction of CBLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 20 publications
3
105
0
6
Order By: Relevance
“…In contrast, Koo et al 10 evaluated the linear bone change, dimensional bone change and the angle between the implant and the adjacent bone through radiographs and found significantly higher bone loss in implants with external connections over those with internal connections. Galindo-Moreno et al 21 also found significantly higher marginal bone loss in implants with external connection (0.714 mm/year) as compared to implants with internal connection (0.516 mm/ year) installed in the mandible after 6 and 18 months.…”
Section: Perimplant Marginal Bone Levelsmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, Koo et al 10 evaluated the linear bone change, dimensional bone change and the angle between the implant and the adjacent bone through radiographs and found significantly higher bone loss in implants with external connections over those with internal connections. Galindo-Moreno et al 21 also found significantly higher marginal bone loss in implants with external connection (0.714 mm/year) as compared to implants with internal connection (0.516 mm/ year) installed in the mandible after 6 and 18 months.…”
Section: Perimplant Marginal Bone Levelsmentioning
confidence: 96%
“…In this respect, many studies have evaluated different types of implant/abutment connections and their effect on the perimplant tissues [9][10] . The main advantages of the conventional external hexagon connection are easy installation of the prosthesis, avoidance of anti-rotational movements and compatibility among different implant systems.…”
Section: Original | Originalmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, those studies do not standardize the implant-supported prosthesis design and the protocol of immediate loading or conventional loading (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%